Dental hygiene workforce issues: a Minnesota study. - Basile SV; Born DO (Journal of Dental Hygiene)
PURPOSE: This study was designed to explore the prevalence and reasons for withdrawal from the dental hygiene workforce. The study also assessed the reasons for maintaining an active license after withdrawal, and the factors that might entice an individual to return to the dental hygiene workforce. METHODS: A random sample was selected of dental hygienists licensed in Minnesota from the November 2003 State Board of Dentistry's dental hygiene licensing file. Data was collected from a mailed questionnaire containing 45 open-ended and close-ended questions. The final sample included 2672 dental hygienists actively licensed and residing in Minnesota. One thousand four hundred and twenty responded to the survey, for a response rate of 53%. From that sample, 129 participants indicated that they were licensed to practice in Minnesota but were not currently working (had withdrawn from the workforce). This study focuses on the responses of those 129 individuals. RESULTS: The prevalence of withdrawal was 9%, with the majority of the participants indicating that they did not plan to return to the dental hygiene workforce. The primary reason for withdrawal was child-rearing responsibilities, followed by health-related reasons, and pursuing a different career. A key difference between those who were active participants in the workforce and those who had withdrawn was related to income. The results of this study found that financial difficulties, death/disability of a spouse, and having older children were the primary factors that would entice a respondent to return as an active participant to the dental hygiene workforce. CONCLUSION: This study suggests that dental hygiene workforce issues are of great complexity and are multifactorial in nature. The findings tend to confirm the results of previous work. It can be concluded that because of the nature of the work and the demands of the profession, it is likely that movement in and out of the dental hygiene workforce will continue to be an issue in the profession.